Model perilaku pencarian informasi dalam memenuhi kebutuhan informasi: Kajian literatur - Fahrun Nisak Alhusna; Siti Masruroh (IJAL (Indonesian Journal of Academic Librarianship), 2021)
The development of information that is getting wider and the need for information is increasing, making information systems play their role as a medium for disseminating information. With various conveniences and a series of information system facilities as a medium for information retrieval, there are various models of information seeking behavior in meeting the need for such information. Especially nowadays people rely more on social media as a place to get information. The need for information arises due to a knowledge gap that arises in a person towards the information needs he needs. Everyone has different information seeking behavior according to their individual needs. There are several characteristics of the information seeking behavior model applied by David Ellis, Wilson, and Kulthau, in meeting information needs.